The Role of Informality in Moderating the Impact of Adverse Macroeconomic Shocks - Sugata Marjit; Ranajoy Bhattacharyya; Lei Yang (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper provides a simple demonstration of an empirical observation pointed out by the existing literature that the presence of informality in the production sector of an economy moderates the impact of economic shocks affecting it. We show that in the presence of informality, adverse demand shocks have a lower impact on aggregate output and adverse supply shocks have a lower impact on prices as well as output. Both would imply that countries without having substantial informal sector, largely more affluent nations, would be exposed more to higher prices following such shocks. This is consistent with contemporary evidence of stagflation in developed countries. Being the residual sector, the informal sector inevitably moves in the opposite direction to the formal sector during a bad shock episode, cushioning its aggregate effect. We then show that the argument goes through if the firms have to finance their working capital requirements by borrowing from the market.
Keywords: E23; E26; E63; 330; informal sector; macroeconomic shocks; stagflation